Studi Implementasi dan Efektivitas TPACK dalam Pembelajaran Maharah Kalam - Laili Mas Uliiyah Hasan (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2023)
Learning Arabic is essential in developing linguistic and cultural competence in the connected global era. To ensure the relevance and effectiveness of Arabic language learning along with the development of information technology, the TPACK (Technological Pedagogical Content Knowledge) approach stands out as the right method. This research explores the implementation and effectiveness of TPACK in Arabic language skills including the speaking skills context. A qualitative approach with descriptive methods was used in this research, by collecting data through literature reviews and observational studies on research relevant to the topic. The research results identified the characteristics of TPACK which are manifested in language skills learning. In speaking skills, various techniques are applied to videos through muhadatsah, munaqasyah, and sardulqissah using the learning.aljazeera.net platform. Analysis of research results shows that the application of TPACK in Arabic language learning can increase student motivation and participation and provide significant assistance to teachers in designing interesting learning experiences. In conclusion, this research highlights the important role of TPACK in the context of Arabic Speaking Skills. The integration of technology in the learning process has been proven to improve the quality of language teaching and learning, offering a more interesting and relevant alternative for students in today's digital era.